2019
DOI: 10.1002/adfm.201901875
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Triggered Polydopamine Secondary Modification: Fast Deposition and Removal of Metal Nanoparticles

Abstract: Since the first report in 2007, polydopamine (PDA) coating has shown great potential as a general and versatile method to create functional nanocoatings on arbitrary substrates. Slow kinetics and poor controllability of the coating and secondary modification processes, however, have limited the further development of this attractive method. In this work, it is demonstrated that UV irradiation at 365 nm significantly accelerates the process of secondary modification of a PDA-coated surface. The kinetics of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Moreover, PDA can act as an extremely versatile and robust platform, which provides connectivity for subsequent modification. [28][29][30][31] . Ou et al [32] have successfully deposited continuous TiO 2 coating onto various PDA-modified polymer substrates including polytetrafluoroethyaylene (PTFE), polyethylene (PE), and polyethylene terephthalate (PET), and studied the biocompatibility of resulting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PDA can act as an extremely versatile and robust platform, which provides connectivity for subsequent modification. [28][29][30][31] . Ou et al [32] have successfully deposited continuous TiO 2 coating onto various PDA-modified polymer substrates including polytetrafluoroethyaylene (PTFE), polyethylene (PE), and polyethylene terephthalate (PET), and studied the biocompatibility of resulting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polydopamine-based adsorbents have abundant functional groups, including phenol groups, catechol, carboxy, o-quinone, amino, imine, which have a strong ability to combine with heavy metals and organic pollutants via chelation, π-π stacking interactions, electrostatic interaction, hydrogen bonding [30]. Moreover, PDA possesses strong reduction ability and has proved effective in reducing some metal ions such as Pt 3+ , Au 3+ and Ag + and graphene oxides [31,32]. Recently, PDA-based functional materials are a kind of adsorbents that have attracted much attention for Cr(VI) removal [25,26,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[231] Very recently, rapidly formed, dynamic, erasable micropatterns have been achieved, through wavelength-selective UVtriggered secondary modification of PDA. [232] The authors demonstrated that 365 nm UV irradiation remarkably increased the kinetics of Michael-addition (or Schiff base reaction) by 12 folds. In addition, the metallization kinetics was accelerated by more than 550 times ( Figure 12B, e).…”
Section: Photolithographymentioning
confidence: 99%